A study to assess the knowledge regarding life style modification of liver cirrhosis among the people in rural area of Udaipur - Chauhan, Manohar Singh (International Journal Of Community Medicine And Public Health, 2025)
Background: This study aimed to assess knowledge about lifestyle modifications for cirrhosis of the liver among the rural population in Udaipur. Cirrhosis is a progressive liver disease requiring timely lifestyle changes for effective management and prevention. Limited awareness and prevalent misconceptions can delay early intervention and affect self-care. The study sought to identify knowledge gaps to inform targeted health education efforts. Methods: A quantitative, descriptive cross-sectional study was conducted in selected rural areas of Udaipur, including Bedla, with 100 participants aged 18 and above selected through convenience sampling. Individuals with other liver diseases or cognitive impairments were excluded. Data were collected via structured interviews and questionnaires and analyzed using SPSS with descriptive statistics and Chi-square tests. Ethical approval was obtained from Tirupati College of Nursing, Pacific Medical University. Results: Participants were predominantly aged 18–25 years (28%), with more males (66%) than females (34%). Most had low education levels 26% had no formal education. A large proportion (80%) lacked awareness about cirrhosis, primary information sources included family (48%) and mass media (24%). Knowledge assessment revealed 55% had inadequate knowledge, 39% moderate and only 6% adequate. Significant associations were found between knowledge and age, gender, education, occupation, marital status, family type, awareness and source of information (p<0.05), while income showed no significant association. Conclusions: There is a clear need for targeted, community-based health education to improve knowledge and promote preventive self-care practices regarding cirrhosis in rural populations.